Parameter and Payload Identification of a 2-DOF Robotic Manipulator: An Algebraic Identification Approach - Páez-García, Julián Y.; Vargas-Tenjo, Laura C.; Charry-Belén, Ricardo A.; Coral-Enriquez, Horacio (Revista Mutis, 2023)
This paper addresses the problem of identifying the parameters and the payloads of a 2-DOF robotic manipulator. The methodology proposed for our research was the algebraic identification method conducted in two stages: First, identifying the parameters of the manipulator and second, identifying the tip payload. Two different numerical simulation cases were used to validate the proposed identification methodology. In both cases, fast convergence was achieved with a low error percentage.